Nasal Nitric Oxide in Relation to Quality-of-life Improvements after Endoscopic Sinus Surgery. Issue 6 (November 2015) - Fu, Chia-Hsiang; Huang, Chi-Che; Chen, Yi-Wei; Chang, Po-Hung; Lee, Ta-Jen
Background: The level of nasal nitric oxide (nNO) in patients with chronic rhinosinusitis (CRS) has been proven to increase after surgical treatment. The relationship between nNO and treatment outcome has not been documented to date. Objective: To evaluate the levels of and changes in nNO after sinus surgery and its effects on quality-of-life improvements for patients with CRS after surgical treatment. Methods: By using a clinical cohort study design, we identified patients who were receiving bilateral endoscopic sinus surgery for CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP) with a 1-year follow-up. We assessed the demographics, preoperative prognostic predictors, pre- and postoperative nNO levels, and disease-related quality of life via a questionnaire. Results: Sixty-nine patients were enrolled, including 53 with CRSwNP and 16 with CRSsNP. The CRSwNP group had lower initial nNO levels and higher endoscopic and image scores but similar demographics and questionnaire scores. In the patients with CRSwNP, nNO levels recovered and reached a plateau at the third month after surgery. However, nNO levels in the CRSsNP group continued to increase until 6 months after surgery before reaching a steady level. Higher preoperative nNO levels were significantly related to better quality-of-life improvements at 3 months after surgery in both groups. Conclusion: The nNO levels in patients with CRS increased and reached a plateau after sinus surgery for both groups. Under similar subjective disease severity, the CRSsNP group had higher preoperative nNO levels and maintained a continuously longer rise before reaching a steady level after surgery. For both CRS groups, a higher initial nNO level brought better quality-of-life improvements and could be provided as a preoperative prognostic indicator.